Manufacturing method of molded body
The method addresses the inefficiencies of conventional papermaking by using a composite of bonding material and inorganic particles with fibers, achieving strong and uniformly bonded molded bodies with reduced water usage.
Patent Information
- Application Number
- JP2021038976
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-11
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-03-11
AI Technical Summary
Conventional papermaking methods require large amounts of water, leading to energy consumption, time, and environmental concerns, and result in molded bodies with inconsistent glue distribution and insufficient strength.
A method for manufacturing molded bodies involving a deposition step with a mixture of fibers and a composite containing bonding material particles and inorganic particles, followed by humidification and heating/pressing to achieve uniform bonding and enhanced strength.
This method allows for the production of molded bodies with excellent strength and uniform glue distribution using minimal water, addressing energy conservation, environmental concerns, and equipment miniaturization.
Smart Images

Figure 0007661727000004 
Figure 0007661727000005 
Figure 0007661727000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a molded article. [Background technology]
[0002] It has been practiced for a long time to deposit fibrous materials and obtain a sheet- or film-like molded product by applying a bonding force between the deposited fibers. A typical example is the production of paper by papermaking using water. Paper produced by papermaking generally has a structure in which, for example, cellulose fibers derived from wood or the like are entangled with each other and partially bound to each other by a binder.
[0003] However, because the papermaking method is a wet process, it requires the use of a large amount of water, and after the paper is formed, it is necessary to dehydrate and dry it, which consumes a lot of energy and time. In addition, the water used must be properly treated as wastewater. Therefore, it is becoming difficult to meet the recent demands for energy conservation and environmental protection. In addition, the equipment used in the papermaking method often requires large utilities such as water, electricity, and drainage facilities, making it difficult to miniaturize it.
[0004] In view of this, a method has been proposed that does not use a large amount of water as in conventional papermaking methods, in which waste paper is broken down into a cotton-like material, a mist of water is added to the material, a powder or granular paste is added, and the material is molded and dried to produce a molded product such as a cushioning material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-246465 Summary of the Invention [Problem to be solved by the invention]
[0006] However, as described above, even if a powdery paste is simply mixed with fibers, it is difficult to uniformly incorporate the paste, and it may be difficult to ensure sufficient strength of the resulting molded body. In particular, when producing paper as a molded body, it is not possible to make it possible to stably pass the paper through a printing machine or printer. [Means for solving the problem]
[0007] The present invention has been made to solve the above-mentioned problems, and can be realized as the following application examples.
[0008] A method for producing a molded body according to an application example of the present invention includes a depositing step of depositing a mixture containing fibers and a composite, a humidifying step of humidifying the mixture; and a molding step of heating and pressurizing the humidified mixture to obtain a molded body, The composite material includes composite particles that integrally include inorganic particles and binder particles that include a binder material that exhibits a bonding force for bonding the fibers together when moisture is applied. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram illustrating a preferred embodiment of a composite used in the method for producing a molded article of the present invention. [Diagram 2] FIG. 2 is a schematic side view showing the configuration of a molding manufacturing apparatus according to a preferred embodiment. [Diagram 3] FIG. 3 is a diagram showing the steps executed by the molding manufacturing apparatus shown in FIG. 2 in order. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Preferred embodiments of the present invention will now be described in detail. [1] Manufacturing method of molded body First, the method for producing the molded article of the present invention will be described.
[0011] The method for producing a molded body of the present invention includes a depositing step of depositing a mixture containing fibers and a composite, a humidifying step of humidifying the mixture, and a molding step of obtaining a molded body by heating and pressurizing the humidified mixture. The composite includes binding material particles containing a binding material that exerts a binding force to bind the fibers together when moisture is added, and inorganic particles.
[0012] This allows the production of a molded body containing fibers and having excellent strength. In addition, a molded body having a desired shape can be suitably produced by using only a small amount of water. In other words, it can be suitably applied to a dry molding method. Therefore, it is advantageous from the viewpoints of productivity and production cost of the molded body, energy saving, and miniaturization of the manufacturing equipment for the molded body. In this specification, the dry molding method refers to a method in which the molding raw material is not immersed in a liquid containing water in the process of producing a molded body, and a method using a small amount of water, for example, a method of spraying a liquid containing water onto the molding raw material, etc., is also included in the dry molding method.
[0013] The above-mentioned excellent effects are believed to be due to the following reasons. That is, by including inorganic particles together with the binder particles, it is possible to effectively prevent the binder particles from unintentionally agglomerating together during storage of the binder material or during transportation of the binder material during the manufacturing process of the molded body, compared to the case where the binder particles are used alone, and the fibers and the binder particles can be uniformly mixed during the manufacturing process of the molded body. In addition, by adding moisture through humidification, the binding force can be exerted, and a molded body having excellent adhesion between the binder material and the fibers can be obtained. As a result, it is possible to suppress unintentional variation in the content of the binder material in the molded body to be manufactured, and it is considered that the strength of the molded body can be excellent.
[0014] As described above, the bonding material may be any material that exhibits a bonding force that bonds fibers together when moisture is added. Here, "exhibiting a bonding force" means that the bonding force is clearly increased compared to when moisture is not added, and does not exclude, for example, cases in which a relatively weak bonding force is obtained when moisture is not added.
[0015] [1-1] Deposition process In the depositing step, a mixture including the fibers and the composite is deposited.
[0016] The mixing ratio of the fibers and the composite in this step is not particularly limited, but the content of the composite in the mixture obtained in this step is preferably 1% by mass or more and 50% by mass or less, more preferably 2% by mass or more and 45% by mass or less, and even more preferably 3% by mass or more and 40% by mass or less.
[0017] This allows the fiber content in the final molded product to be sufficiently high, while improving the strength of the molded product, and also allows the composite to be transported more smoothly during the manufacturing process of the molded product.
[0018] The fibers to be mixed with the composite in this step may be ones that have been subjected to a moistening treatment in advance, for example, prior to the moistening step described below, i.e., the step of moistening the mixture. Also, the fibers may be moistened during the period between mixing with the composite and deposition of the mixture obtained by this mixing.
[0019] In the above cases, the moisture content in the fibers subjected to this step is preferably 0.1% by mass or more and 12% by mass or less, more preferably 0.2% by mass or more and 10% by mass or less, and even more preferably 0.3% by mass or more and 9.0% by mass or less.
[0020] This makes it possible, for example, to effectively prevent the fibers from being adversely affected by static electricity before this process, such as the fibers sticking to the wall surfaces of the molding production equipment due to static electricity, and also makes it possible to mix the fibers and the composite more uniformly.
[0021] [1-1-1] Fiber Fibers are usually the main component of the molded body produced using the molded body production method of the present invention, and are a component that greatly contributes to maintaining the shape of the molded body and also has a significant effect on the properties of the molded body, such as its strength.
[0022] The fibers may be made of any material, but it is preferable that the material be capable of maintaining the fibrous state even when heated during the molding process.
[0023] In particular, the fibers are preferably made of a substance containing at least one chemical structure selected from the group consisting of a hydroxyl group, a carbonyl group, and an amino group.
[0024] As a result, for example, when starch is used as the binding material, hydrogen bonds are more easily formed between the fibers and the binding material, improving the bonding strength between the fibers and the binding material and improving the strength of the molded body as a whole, for example the tensile strength of a sheet-like molded body.
[0025] The fibers may be synthetic fibers composed of synthetic resins such as polypropylene, polyester, polyurethane, etc., but are preferably naturally derived fibers, i.e., biomass derived fibers, and more preferably cellulose fibers.
[0026] This makes it possible to more appropriately address environmental issues and conserve natural resources. In particular, when the fibers are cellulose fibers, the following effects can be obtained.
[0027] That is, cellulose is an abundant natural material derived from plants, and the use of cellulose as a fiber can more appropriately address environmental issues and save buried resources, etc., and is also preferable from the viewpoints of stable supply of molded products, cost reduction, etc. Furthermore, among various fibers, cellulose fibers have particularly high theoretical strength, and are advantageous from the viewpoint of further improving the strength of molded products.
[0028] Cellulosic fibers are generally composed mainly of cellulose, but may contain components other than cellulose, such as hemicellulose and lignin. The cellulose fibers used may be those that have been subjected to a treatment such as bleaching.
[0029] The fibers may also be treated with ultraviolet light, ozone, plasma, or other such treatments. This can increase the hydrophilicity of the fibers and enhance their affinity with the binding material. More specifically, these treatments can introduce functional groups such as hydroxyl groups onto the fiber surface, allowing the fibers to form hydrogen bonds more efficiently with the binding material.
[0030] The average length of the fibers is not particularly limited, but is preferably from 0.1 mm to 50 mm, more preferably from 0.2 mm to 5.0 mm, and even more preferably from 0.3 mm to 3.0 mm.
[0031] This makes it possible to improve the stability of shape, strength, etc. of the produced molded article.
[0032] The average thickness of the fibers is not particularly limited, but is preferably 0.005 mm or more and 0.5 mm or less, and more preferably 0.010 mm or more and 0.05 mm or less.
[0033] This makes it possible to improve the stability of the shape, strength, etc. of the produced molded article. In addition, it is possible to more effectively prevent the occurrence of undesired irregularities on the surface of the molded article.
[0034] The average aspect ratio of the fibers, that is, the average length to the average thickness, is not particularly limited, but is preferably 10 or more and 1,000 or less, and more preferably 15 or more and 500 or less.
[0035] This makes it possible to improve the stability of the shape, strength, etc. of the produced molded article. In addition, it is possible to more effectively prevent the occurrence of undesired irregularities on the surface of the produced molded article.
[0036] [1-1-2] Complex The composite material mixed with the fibers will be described in detail below. FIG. 1 is a diagram illustrating a preferred embodiment of a composite used in the method for producing a molded article of the present invention.
[0037] As described above, the composite C10 includes composite particles C1 that integrally include inorganic particles C3 and binding material particles C2 that contain a binding material that exhibits a bonding force that bonds fibers together when moisture is added. Note that in the present invention, the term "integrally includes" refers to a state in which at least a portion of the inorganic particles C3 is attached to the surface or inside of the binding material particles C2 to form the composite particles C1, and does not exclude the presence of binding material particles C2 and inorganic particles C3 that do not form the composite particles C1 in the composite 10.
[0038] In particular, in the illustrated configuration, a composite particle C1 contained in a composite C10 has inorganic particles C3 attached to the surfaces of binding material particles C2.
[0039] This causes a repulsive force between the inorganic particles C3, making it more difficult for the binding material particles C2 to aggregate with each other. The arrangement of the inorganic particles C3 can be confirmed, for example, by various electron microscopes.
[0040] [1-1-2-1] Composite particles The composite particle C1 contained in the composite C10 may be a single inorganic particle C3 attached to the surface of a single binding material particle C2, but the composite particle C1 includes a particle in which multiple inorganic particles C3 are attached to the surface of a single binding material particle C2. This makes the above-mentioned effects more pronounced.
[0041] The average particle size of the composite particles C1 is preferably 1.0 μm or more and 100 μm or less, more preferably 2.0 μm or more and 70 μm or less, and even more preferably 3.0 μm or more and 50 μm or less. This makes the above-mentioned effects more pronounced.
[0042] In this specification, the average particle size refers to the median diameter (D50 value of cumulative 50% frequency) unless otherwise specified. The average particle size can be determined, for example, by measurement using a Microtrack UPA (manufactured by Nikkiso Co., Ltd.).
[0043] [1-1-2-1-1]Binding material particles The binding material particles C2 contain a binding material that exerts a binding force for binding the fibers together when moisture is applied.
[0044] Examples of the binding material constituting the binding material particle C2 include naturally occurring components such as starch, dextrin, glycogen, amylose, hyaluronic acid, kudzu, konjac, potato starch, etherified starch, esterified starch, natural gum paste (etherified tamarind gum, etherified locust bean gum, etherified guar gum, acacia arabic gum), fiber-derived paste (etherified carboxymethylcellulose, hydroxyethylcellulose), seaweed (sodium alginate, agar), animal protein (collagen, gelatin, hydrolyzed collagen, sericin), polyvinyl alcohol, polyacrylic acid, polyacrylamide, etc., and one or more selected from these may be used in combination, but naturally occurring components are preferred, and starch is more preferred.
[0045] This makes it possible to suppress the use of petroleum-derived materials and reduce CO2 emissions while still achieving the excellent effects of the present invention as described above. In addition, such materials are also highly biodegradable.
[0046] In particular, starch is a material that exhibits favorable bonding strength as gelatinization proceeds when heated after the addition of moisture, i.e., it is a binding material that exhibits favorable bonding strength for bonding fibers together when moisture is added. Starch also exhibits bonding strength through non-covalent bonds such as hydrogen bonds between fibers, particularly fibers made of materials having functional groups such as hydroxyl groups, such as cellulose fibers, and has excellent bonding strength with fibers and excellent covering properties for fibers, which can improve the strength, etc., of molded articles produced using the composite C10.
[0047] In particular, the binding material is preferably starch having a weight average molecular weight of 50,000 or more and 400,000 or less.
[0048] This allows the water absorption efficiency of the binding material to be improved, and even when a smaller amount of water is added, a molded body with sufficient strength can be produced. More specifically, even when a small amount of water is added, the gelatinization by heating proceeds favorably, and the productivity of molded bodies using the complex C10 can be improved, and the strength of the molded bodies produced can be improved. In addition, starch with a predetermined molecular weight as described above is particularly unlikely to be undesirably denatured by the addition of water.
[0049] Starch having a weight-average molecular weight controlled to a value within a predetermined range can be preferably obtained, for example, as follows. For example, natural starch is suspended in water, and then sulfuric acid, hydrochloric acid, or sodium hypochlorite is allowed to act on the starch under conditions that do not gelatinize the starch, thereby obtaining starch having a weight-average molecular weight controlled to a value within a predetermined range. Also, for example, natural starch is directly added, or a very small amount of volatile acid such as hydrochloric acid is diluted with water and added, thoroughly mixed, aged, dried at a low temperature, and then heated to 120 to 180°C, thereby obtaining starch having a weight-average molecular weight controlled to a value within a predetermined range. Also, for example, starch having a weight-average molecular weight controlled to a value within a predetermined range can be preferably obtained by subjecting a paste liquid obtained by heating natural starch together with water to a treatment of hydrolysis with an acid or enzyme.
[0050] As described above, the weight average molecular weight of the starch used as the binding material is preferably 50,000 or more and 400,000 or less, more preferably 70,000 or more and 300,000 or less, and even more preferably 80,000 or more and 200,000 or less. This makes the above-mentioned effects more pronounced.
[0051] The weight-average molecular weight of starch can be determined by gel permeation chromatography. The weight-average molecular weights shown in the examples described later are also values determined by gel permeation chromatography.
[0052] Starch is a polymeric material in which multiple α-glucose molecules are polymerized through glycosidic bonds. Starch contains at least one of amylose and amylopectin.
[0053] The binder particles C2 may contain, in addition to the binder, a component other than the binder, i.e., a component that does not exert a bonding force to bond fibers together even when moisture is added, such as, for example, fiber materials, pigments, dyes, toners, and other coloring materials.
[0054] However, the content of the binding material in the binding material particles C2 is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0055] The average particle size of the binding material particles C2 is preferably 1.0 μm or more and 50 μm or less, more preferably 3.0 μm or more and 40 μm or less, and even more preferably 5.0 μm or more and 30 μm or less.
[0056] This allows the fibers and the composite C10 to be mixed more uniformly, and the moisture absorption in the humidification process proceeds more smoothly, resulting in a molded body with better strength and reliability. In addition, when the particle size of the binding material particles C2 is relatively small, the ratio of the surface area to the mass of the binding material particles C2 is increased, and the water absorption efficiency of the binding material is improved. As a result, even when the amount of moisture added is small, a molded body with sufficient strength can be manufactured. In addition, the fluidity and ease of handling of the composite C10 are further improved. In addition, when the binding material particles having such a small average particle size are not coexisted with the inorganic particles, the aggregation of the binding material particles is particularly likely to occur, but in the present invention, such a problem can be suitably prevented by using a composite in which the binding material particles and the inorganic particles coexist. That is, when the average particle size of the binding material particles C2 is within the above range, the effect of the present invention is more significantly exhibited.
[0057] The composite C10 may contain binding material particles C2 that do not have inorganic particles C3 attached, in other words, binding material particles C2 that do not constitute composite particles C1, but the proportion of the binding material particles C2 that constitute composite particles C1 to the total binding material particles C2 contained in the composite C10 is preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 70 mass% or more. This allows the above-mentioned effects of the present invention to be more pronounced.
[0058] [1-1-2-1-2]Inorganic particles The composite particle C1 contains an inorganic particle C3.
[0059] The average particle size of the inorganic particles C3 is preferably 1 nm or more and 20 nm or less, and more preferably 5 nm or more and 18 nm or less.
[0060] This allows the above-mentioned effect of containing the inorganic particles C3 to be more prominent. In addition, the surface of the composite particle C1 in which the inorganic particles C3 are attached to the surface of the binding material particles C2 can be suitably prevented from becoming excessively uneven, and the fluidity of the composite C10 can be made more excellent. In addition, the inorganic particles C3 can be more suitably attached to the surface of the binding material particles C2, and the inorganic particles C3 can be more suitably prevented from unintentionally falling off from the surface of the binding material particles C2 or being unintentionally buried inside the binding material particles C2, and the above-mentioned effect of containing the composite particles C1 can be more prominently exhibited.
[0061] The composite C10 may contain inorganic particles C3 that are not attached to binding material particles C2, in other words, inorganic particles C3 that do not constitute composite particle C1. However, the proportion of inorganic particles C3 that constitute composite particle C1 to the total inorganic particles C3 contained in composite C10 is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. This allows the above-mentioned effects of the present invention to be more pronounced.
[0062] The inorganic particles C3 may be any particles as long as they are mainly composed of an inorganic material. Furthermore, the inorganic particles C3 may have a substantially uniform composition in each portion, or may have portions with different compositions.
[0063] More specifically, for example, the inorganic particles C3 may be base particles that have been surface-treated with at least one type of surface treatment agent. In other words, the inorganic particles C3 may have base particles made of an inorganic material and a coating layer made of a surface treatment agent that coats the base particles.
[0064] This makes it possible, for example, to more effectively prevent undesired aggregation of the binding material particles C2, improve the wetting and spreading of the binding material on the fiber surfaces during the molding process, and improve the strength of the final molded body.
[0065] Hereinafter, the composite C10 will be mainly described as including inorganic particles C3 each having a base particle made of an inorganic material and a coating layer made of a surface treatment agent that coats the base particle.
[0066] [1-1-2-1-2-1]Mother particle The base particles of the inorganic particles C3, in other words, the base material of the inorganic particles C3 that has been surface-treated with a surface treatment agent, is composed of an inorganic material.
[0067] This makes it possible to provide the inorganic particles C3 with better heat resistance, and the above-mentioned effects are more reliably achieved.
[0068] Examples of materials constituting the base particles of the inorganic particles C3 include various metal materials, various metal compounds, various glass materials, and various carbon materials.
[0069] Examples of the metal material include elemental metals such as Fe, Al, Cu, Ag, and Ni, and alloys containing at least one of these metals.
[0070] Examples of the metal compound include metal oxides, metal nitrides, metal carbides, and metal sulfides, and more specifically, examples of the metal compound include silica, alumina, zirconia, titanium oxide, magnetite, and ferrite.
[0071] Examples of glass materials include soda glass, crystalline glass, quartz glass, lead glass, potassium glass, borosilicate glass, and non-alkali glass.
[0072] Examples of carbon materials include diamond, carbon fiber, carbon black, carbon nanotubes, carbon nanofibers, and fullerene.
[0073] Among these, silica is preferred as the constituent material of the base particles of the inorganic particles C3, in other words, the inorganic particles C3 are preferably made of a material containing silica.
[0074] This allows the surface treatment of the base particles with the surface treatment agent to be more suitably performed, and the adhesion between the base particles and the surface treatment agent can be improved. As a result, the above-mentioned effects are more prominent. In addition, silica is a material that is unlikely to adversely affect the color of the molded product produced using the composite C10. In particular, when the molded product is paper, such effects are more prominent.
[0075] The base particles of the inorganic particles C3 may be composed mainly of the inorganic material, and may contain an organic material in addition to the inorganic material.
[0076] However, the content of the inorganic material in the base particle of the inorganic particle C3 is preferably 90 mass % or more, more preferably 92 mass % or more, and even more preferably 95 mass % or more.
[0077] [1-1-2-1-2-2] Surface treatment agent As described above, the inorganic particles C3 preferably have base particles made of an inorganic material and a coating layer made of a surface treatment agent that coats the base particles.
[0078] Examples of preferred surface treatment agents include fluorine-containing compounds and silicon-containing compounds. By using such a surface treatment agent, the aggregation of the binding material particles C2 and the composite particles C1 is more suitably prevented. In addition, by containing the inorganic particles C3 that have been surface-treated with the above-mentioned surface treatment agent, the fluidity and ease of handling of the composite C10 are improved. This makes it possible to particularly improve the productivity of the molded body. In addition, the surface free energy of the inorganic particles C3 can be more efficiently reduced. As a result, in the molding process, the composite C10 is more likely to wet and spread on the surface of the fibers. This makes it possible to improve the adhesion between the fibers and the binding material in the finally obtained molded body, and to improve the strength of the molded body.
[0079] Examples of the fluorine-containing compound include perfluoropolyether and fluorine-modified silicone oil.
[0080] Examples of the silicon-containing compound include various silicone oils such as polydimethylsiloxane having a trimethylsilyl end, polydimethylsiloxane having a hydroxyl end, polymethylphenylsiloxane, amino-modified silicone oil, epoxy-modified silicone oil, carboxy-modified silicone oil, carbinol-modified silicone oil, polyether-modified silicone oil, and alkyl-modified silicone oil.
[0081] Among them, the surface treatment agent is preferably polydimethylsiloxane having a trimethylsilyl end group, in other words, the inorganic particles preferably have trimethylsilyl groups on the surface.
[0082] This makes it possible to more effectively prevent aggregation of the composite particles C1, the binding material particles C2, and the inorganic particles C3.
[0083] When a surface treatment agent is used, one type of surface treatment agent may be used, or multiple types of surface treatment agents may be used.
[0084] When a plurality of types of surface treatment agents are used, the plurality of types of surface treatment agents may be used for a single base particle, or the composite C10 may contain, as the inorganic particles C3, particles treated with different surface treatment agents.
[0085] The content of the surface treatment agent relative to 100 parts by mass of the base particles contained in the composite C10 is preferably from 0.5 to 7 parts by mass, and more preferably from 1 to 5 parts by mass. This allows the above-mentioned effects of the present invention to be more pronounced.
[0086] [1-1-2-2] Other configurations The composite C10 may include the composite particle C1 described above and may further include other components. For example, the composite C10 may include, in addition to the composite particle C1 described above, binding material particles C2 to which inorganic particles C3 are not attached, or inorganic particles C3 to which binding material particles C2 are not attached.
[0087] However, the content of the composite particles C1 in the composite C10 is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. This makes the above-mentioned effects more pronounced.
[0088] [1-1-2-3] Other conditions It is preferable that the complex C10 satisfies the following conditions.
[0089] For example, the content of the binding material particles C2 in the composite C10 is preferably 90.0% by mass or more and 99.9% by mass or less, more preferably 95.0% by mass or more and 99.7% by mass or less, and even more preferably 97.0% by mass or more and 99.4% by mass or less. This makes the above-mentioned effects more pronounced.
[0090] The content of inorganic particles C3 in composite C10 is preferably 0.1% by mass to 10.0% by mass, more preferably 0.3% by mass to 5.0% by mass, and even more preferably 0.6% by mass to 3.0% by mass.
[0091] This makes it possible to more significantly exhibit the effects of including the inorganic particles C3 as described above, thereby making it possible to improve the fluidity of the composite C10 and to improve the strength of the finally obtained molded body.
[0092] [1-2] Humidification process In the wetting step, the deposited mixture, i.e., the mixture containing the fibers and the composite C10, is wetting.
[0093] This makes it possible to improve the bonding strength between the fibers and the binder material and between the fibers via the starch in the molding step described below, and to improve the strength of the finally obtained molded product. Also, molding in the molding step can be preferably performed under relatively mild conditions.
[0094] The method of humidifying the mixture is not particularly limited, but is preferably performed without contact with the mixture. For example, the method includes placing the mixture in a high humidity atmosphere, passing the mixture through a high humidity space, spraying a mist of a liquid containing water onto the mixture, and passing the mixture through a space in which a mist of a liquid containing water is suspended. One or more methods selected from these can be combined. More specifically, the mixture can be humidified using various humidifiers such as an evaporation type or an ultrasonic type. The mixture can be humidified at multiple stages, for example, in the process of producing a molded body. The liquid containing water may contain, for example, a preservative, a fungicide, an insecticide, etc.
[0095] The amount of water added to the mixture in the humidification step is not particularly limited, but it is preferable to add 1 part by mass or more and 50 parts by mass or less of water, more preferably 5 parts by mass or more and 40 parts by mass or less of water, and even more preferably 10 parts by mass or more and 30 parts by mass or less of water, per 100 parts by mass of the mixture subjected to the humidification step.
[0096] This makes it possible to produce a molded product having sufficient strength with significantly less water than in the conventional papermaking methods, and allows the effects of the present invention to be more pronounced.
[0097] [1-3] Molding process In the molding step, the mixture moistened in the moistening step is heated and pressurized to obtain a molded body. The moistening step and the molding step may be performed simultaneously.
[0098] The heating temperature in the molding step is not particularly limited, but is preferably from 60°C to 250°C, more preferably from 70°C to 200°C, and even more preferably from 80°C to 170°C.
[0099] This allows the composite C10 to be more suitably spread on the surface of the fibers while effectively preventing unintended deterioration, denaturation, etc. of the components of the fibers and the composite C10. As a result, the strength and reliability of the molded body to be manufactured can be improved. This is also preferable from the viewpoint of energy saving. In particular, when the binding material particles C2 are composed of a material containing starch as a binding material, it is possible to suitably advance the gelatinization of the starch that has absorbed water, and it is possible to effectively prevent unintended deterioration, etc. of the constituent materials of the molded body.
[0100] The pressure applied to the mixture in the molding step is not particularly limited, but is preferably from 0.1 MPa to 100 MPa, and more preferably from 0.3 MPa to 80 MPa.
[0101] This allows the composite C10 to more suitably spread over the fiber surface, resulting in a molded article with superior strength.
[0102] This allows the composite C10 to be more suitably spread on the surface of the fibers while effectively preventing undesired deterioration, denaturation, etc. of the components of the fibers and the composite C10. As a result, the strength and reliability of the produced molded article can be improved. This is also preferable from the viewpoint of energy saving. This step can be carried out using, for example, a heat press, a heat roller, or the like.
[0103] The method for producing a molded article of the present invention can be suitably carried out, for example, by using a molded article production apparatus described below.
[0104] [2] Molded body manufacturing equipment Next, the apparatus for producing a molded article according to the present invention will be described.
[0105] Fig. 2 is a schematic side view showing the configuration of a molded body manufacturing apparatus of a preferred embodiment. Fig. 3 is a view showing the steps executed by the molded body manufacturing apparatus shown in Fig. 2 in order. For convenience of explanation, the upper side in Fig. 2 may be referred to as "upper" or "upper side", the lower side as "lower" or "lower", the left side as "left" or "upstream side", and the right side as "right" or "downstream side".
[0106] In the following description, an example of a sheet manufacturing apparatus that manufactures a sheet as a molded body will be described as an example of a molded body manufacturing apparatus.
[0107] 2, the sheet manufacturing apparatus 100, which is an apparatus for manufacturing a formed body, includes a raw material supplying section 11, a coarse crushing section 12, a defibrating section 13, a sorting section 14, a first web forming section 15, a fine dividing section 16, a mixing section 17, a refining section 18, a second web forming section 19, a sheet forming section 20, a cutting section 21, and a stocking section 22. The sheet manufacturing apparatus 100 also includes a humidifying section 231, a humidifying section 232, a humidifying section 233, and a humidifying section 234.
[0108] The operation of each part of the sheet manufacturing apparatus 100 is controlled by a control part (not shown).
[0109] 3, in this embodiment, the method for manufacturing a sheet, which is a formed body, includes a raw material supplying process, a coarse crushing process, a defibrating process, a sorting process, a first web forming process, a dividing process, a mixing process, a loosening process, a second web forming process, a moistening process, a sheet forming process, and a cutting process. The sheet manufacturing apparatus 100 can execute these processes in order.
[0110] The configuration of each part of the sheet manufacturing apparatus 100 will be described below. The raw material supplying section 11 is a section that performs a raw material supplying step of supplying a sheet material M1 to the crushing section 12. This sheet material M1 is a sheet material that contains fibers such as cellulose fibers.
[0111] The crushing unit 12 is a section that performs a crushing step of crushing the sheet material M1 supplied from the raw material supply unit 11 in air or the like. The crushing unit 12 has a pair of crushing blades 121 and a hopper 122.
[0112] The pair of crushing blades 121 rotate in opposite directions to each other, and can crush, i.e., cut, the sheet-like material M1 between them into crushed pieces M2. The shape and size of the crushed pieces M2 are preferably suitable for defibration processing in the defibration unit 13, and are preferably small pieces with a side length of 100 mm or less, and more preferably 10 mm or more and 70 mm or less.
[0113] The hopper 122 is disposed below the pair of crushing blades 121 and has, for example, a funnel shape. This allows the hopper 122 to receive the coarsely crushed pieces M2 that have been crushed by the crushing blades 121 and dropped.
[0114] In addition, above the hopper 122, a humidifying section 231 is disposed adjacent to the pair of coarse crushing blades 121. The humidifying section 231 humidifies the coarsely crushed pieces M2 in the hopper 122. The humidifying section 231 has a filter (not shown) that contains moisture, and is configured as an evaporation-type humidifier that supplies humidified air with increased humidity to the coarsely crushed pieces M2 by passing air through the filter. By supplying the humidified air to the coarsely crushed pieces M2, it is possible to prevent the coarsely crushed pieces M2 from adhering to the hopper 122, etc. due to static electricity.
[0115] The hopper 122 is connected to the defibrating unit 13 via a pipe 241, which is a flow path. The coarse crushed pieces M2 collected in the hopper 122 pass through the pipe 241 and are transported to the defibrating unit 13.
[0116] The defibrating unit 13 is a part that performs a defibrating process in which the coarsely crushed pieces M2 are defibrated in air, i.e., in a dry manner. The defibrating process in this defibrating unit 13 can generate a defibrated material M3 from the coarsely crushed pieces M2. Here, "defibrating" refers to untangling the coarsely crushed pieces M2, which are made up of multiple fibers bound together, into individual fibers. This untangled material becomes the defibrated material M3. The shape of the defibrated material M3 is linear or band-like. The defibrated material M3 may also be present in a state where it is entangled with other pieces to form a mass, that is, in a state where it forms so-called "lumps."
[0117] In this embodiment, for example, the defibrating unit 13 is configured with an impeller mill having a rotor that rotates at high speed and a liner located on the outer periphery of the rotor. The coarse fragments M2 that flow into the defibrating unit 13 are sandwiched between the rotor and the liner and defibrated.
[0118] Furthermore, the defibrating unit 13 can generate an air flow from the crushing unit 12 to the sorting unit 14, i.e., an airflow, by the rotation of the rotor. This allows the coarsely crushed pieces M2 to be sucked into the defibrating unit 13 from the pipe 241. Furthermore, after the defibrating process, the defibrated material M3 can be sent to the sorting unit 14 via the pipe 242.
[0119] A blower 261 is installed in the middle of the pipe 242. The blower 261 is an airflow generating device that generates an airflow toward the screening section 14. This promotes the sending out of the defibrated material M3 to the screening section 14.
[0120] The sorting unit 14 is a section that performs a sorting process in which the defibrated material M3 is sorted according to the length of the fibers. In the sorting unit 14, the defibrated material M3 is sorted into a first sorted material M4-1 and a second sorted material M4-2 that is larger than the first sorted material M4-1. The first sorted material M4-1 has a size suitable for the subsequent production of the sheet S. The second sorted material M4-2 includes, for example, material that is insufficiently defibrated and material in which defibrated fibers have excessively aggregated together.
[0121] The sorting unit 14 has a drum unit 141 and a housing unit 142 that houses the drum unit 141.
[0122] The drum part 141 is a sieve composed of a cylindrical mesh body and rotates around its central axis. The defibrated material M3 flows into this drum part 141. Then, as the drum part 141 rotates, the defibrated material M3 smaller than the mesh opening is sorted as the first sorted material M4-1, and the defibrated material M3 larger than the mesh opening is sorted as the second sorted material M4-2. The first sorted item M4-1 falls from the drum portion 141.
[0123] Meanwhile, the second sorted material M4-2 is sent to pipe 243, which is a flow path connected to the drum unit 141. Pipe 243 is connected to pipe 241 on the opposite side to the drum unit 141, i.e., the upstream side. The second sorted material M4-2 that passes through this pipe 243 merges with the coarsely crushed pieces M2 in pipe 241 and flows into the defibrating unit 13 together with the coarsely crushed pieces M2. As a result, the second sorted material M4-2 is returned to the defibrating unit 13 and is defibrated together with the coarsely crushed pieces M2.
[0124] The first selected material M4-1 from the drum unit 141 falls while being dispersed in the air, and heads toward the first web forming unit 15, which is a separation unit located below the drum unit 141. The first web forming unit 15 is a unit that performs a first web forming step of forming the first web M5 from the first selected material M4-1. The first web forming unit 15 has a mesh belt 151, which is a separation belt, three tension rollers 152, and a suction unit 153.
[0125] The mesh belt 151 is an endless belt on which the first sorted material M4-1 is accumulated. The mesh belt 151 is wound around three tension rollers 152. As the tension rollers 152 rotate, the first sorted material M4-1 on the mesh belt 151 is transported downstream.
[0126] The size of the first sorted material M4-1 is equal to or larger than the mesh size of the mesh belt 151. This restricts the passage of the first sorted material M4-1 through the mesh belt 151, and therefore the first sorted material M4-1 can be piled up on the mesh belt 151. Furthermore, the first sorted material M4-1 is transported downstream together with the mesh belt 151 while being piled up on the mesh belt 151, and is thus formed as a layered first web M5.
[0127] Furthermore, the first sorted material M4-1 may contain, for example, dust and dirt. For example, dust and dirt may be mixed in together with the sheet material M1 when the sheet material M1 is supplied from the raw material supply section 11 to the crushing section 12. The dust and dirt are smaller than the mesh size of the mesh belt 151. As a result, the dust and dirt pass through the mesh belt 151 and fall further downward.
[0128] The suction section 153 can suck air from below the mesh belt 151. This makes it possible to suck in dust and dirt that has passed through the mesh belt 151 together with the air.
[0129] In addition, the suction unit 153 is connected to the collection unit 27 via a pipe 244 which is a flow path. The dust and dirt sucked by the suction unit 153 is collected in the collection unit 27.
[0130] A pipe 245, which is a flow path, is further connected to the collection unit 27. A blower 262 is installed midway through the pipe 245. By operating the blower 262, a suction force can be generated in the suction unit 153. This promotes the formation of the first web M5 on the mesh belt 151. Dust and dirt are removed from this first web M5. By operating the blower 262, the dust and dirt pass through the pipe 244 and reach the collection unit 27.
[0131] The housing part 142 is connected to the humidifier part 232. The humidifier part 232 is configured as an evaporative humidifier similar to the humidifier part 231. This allows humidified air to be supplied into the housing part 142. The first sorted item M4-1 can be humidified by this humidified air, and therefore, the first sorted item M4-1 can be prevented from adhering to the inner wall of the housing part 142 due to electrostatic force.
[0132] A humidifying section 235 is disposed downstream of the sorting section 14. The humidifying section 235 is configured with an ultrasonic humidifier that sprays water. This allows moisture to be supplied to the first web M5, and thus the moisture content of the first web M5 is adjusted. This adjustment makes it possible to suppress adhesion of the first web M5 to the mesh belt 151 due to electrostatic force. As a result, the first web M5 is easily peeled off from the mesh belt 151 at the position where the mesh belt 151 is folded back by the tension roller 152.
[0133] The segmentation unit 16 is disposed downstream of the humidification unit 235. The segmentation unit 16 is a section that performs a segmentation step of segmenting the first web M5 peeled off from the mesh belt 151. The segmentation unit 16 has a rotatably supported propeller 161 and a housing portion 162 that houses the propeller 161. The first web M5 is wound around the rotating propeller 161, so that the first web M5 can be segmented. The segmented first web M5 becomes segmented bodies M6. The segmented bodies M6 move down inside the housing portion 162.
[0134] The housing part 162 is connected to the humidifier part 233. The humidifier part 233 is configured with an evaporation type humidifier similar to the humidifier part 231. This allows humidified air to be supplied into the housing part 162. This humidified air can also prevent the fragmented bodies M6 from adhering to the propeller 161 and the inner wall of the housing part 162 due to electrostatic force.
[0135] A mixer 17 is disposed downstream of the subdivision section 16. The mixer 17 is a section that performs a mixing step of mixing the fragmented bodies M6 with the above-mentioned complex C10. The mixer 17 has a complex supply section 171, a pipe 172 that is a flow path, and a blower 173.
[0136] The pipe 172 connects the housing portion 162 of the subdivision section 16 and the housing portion 182 of the disintegration section 18, and is a flow path through which the mixture M7 of the subdivision bodies M6 and the complexes C10 passes.
[0137] A composite material supplying section 171 is connected to the middle of the pipe 172. The composite material supplying section 171 has a screw feeder 174. The screw feeder 174 is driven to rotate, thereby supplying the composite material C10 to the pipe 172. The composite material C10 supplied to the pipe 172 is mixed with the fragmented bodies M6 to become the mixture M7.
[0138] In addition, the composite supply unit 171 may contain, together with the composite C10, for example, a colorant for coloring the fibers, an aggregation inhibitor for inhibiting aggregation of the fibers or aggregation of the composite C10, and a flame retardant for making the fibers, etc. less flammable.
[0139] Further, a blower 173 is provided in the middle of the pipe 172, downstream of the complex supply unit 171. The blower 173 can generate an airflow toward the disintegrating unit 18. This airflow can agitate the fragmented bodies M6 and the complex C10 in the pipe 172. This allows the mixture M7 to flow into the disintegrating unit 18 in a state in which the fragmented bodies M6 and the complex C10 are uniformly dispersed. Furthermore, the fragmented bodies M6 in the mixture M7 are disintegrated in the process of passing through the pipe 172, becoming finer fibrous.
[0140] The disentanglement unit 18 is a unit that performs a disentanglement step of disentangling entangled fibers in the mixture M7. The disentanglement unit 18 has a drum unit 181 and a housing unit 182 that houses the drum unit 181.
[0141] The drum section 181 is a sieve that is composed of a cylindrical mesh body and rotates around its central axis. The mixture M7 flows into the drum section 181. As the drum section 181 rotates, fibers and the like of the mixture M7 that are smaller than the mesh openings can pass through the drum section 181. At that time, the mixture M7 is loosened.
[0142] Furthermore, the mixture M7 loosened by the drum section 181 falls while being dispersed in the air, and heads toward the second web forming section 19 located below the drum section 181. The second web forming section 19 is a section where a second web forming step is performed in which a second web M8 is formed from the mixture M7. The second web forming step in this embodiment is a deposition step in which a mixture containing fibers and a composite C10 is deposited. The second web forming section 19 has a mesh belt 191 which is a separation belt, a tension roller 192, and a suction section 193.
[0143] The mesh belt 191 is an endless belt on which the mixture M7 is accumulated. The mesh belt 191 is wound around four tension rollers 192. The mixture M7 on the mesh belt 191 is transported downstream by the rotation of the tension rollers 192.
[0144] Moreover, most of the mixture M7 on the mesh belt 191 has a size equal to or larger than the mesh openings of the mesh belt 191. This prevents the mixture M7 from passing through the mesh belt 191, and therefore the mixture M7 can be accumulated on the mesh belt 191. Moreover, the mixture M7 is transported downstream together with the mesh belt 191 while being accumulated on the mesh belt 191, and is thus formed as a layered second web M8.
[0145] The suction unit 193 can suck air from below the mesh belt 191. This allows the mixture M7 to be sucked onto the mesh belt 191, thereby facilitating the accumulation of the mixture M7 on the mesh belt 191.
[0146] A pipe 246, which is a flow path, is connected to the suction unit 193. A blower 263 is provided midway through the pipe 246. By operating the blower 263, the suction unit 193 can generate a suction force.
[0147] The housing part 182 is connected to the humidifier part 234. The humidifier part 234 is configured as an evaporation type humidifier similar to the humidifier part 231. This allows humidified air to be supplied into the housing part 182. The inside of the housing part 182 can be humidified by this humidified air, and therefore, it is also possible to prevent the mixture M7 from adhering to the inner wall of the housing part 182 due to electrostatic force.
[0148] The humidifying section 236 is disposed downstream of the loosening section 18. The humidifying section 236 is a section where the humidifying step described above is performed. The humidifying section 236 is configured with an ultrasonic humidifier similar to the humidifying section 235. This allows moisture to be supplied to the second web M8, and thus the moisture content of the second web M8 is adjusted. This adjustment allows the bonding strength between the fibers and the bonding material in the sheet S as the finally obtained molded body to be favorable. In addition, the adhesion of the second web M8 to the mesh belt 191 due to electrostatic force can be suppressed. This allows the second web M8 to be easily peeled off from the mesh belt 191 at the position where the mesh belt 191 is folded back by the tension roller 192.
[0149] A sheet forming unit 20 is disposed downstream of the second web forming unit 19. The sheet forming unit 20 is a section that performs a sheet forming process, which is a molding process for forming a sheet S from the second web M8. The sheet forming unit 20 has a pressurizing unit 201 and a heating unit 202.
[0150] The pressurizing unit 201 has a pair of calender rollers 203, and can pressurize the second web M8 between them without heating it. This increases the density of the second web M8. Then, the second web M8 is transported toward the heating unit 202. One of the pair of calender rollers 203 is a driven roller driven by the operation of a motor (not shown), and the other is a driven roller.
[0151] The heating section 202 has a pair of heating rollers 204, and can apply pressure to the second web M8 while heating it therebetween. This heating and pressurization causes the composite C10 to melt in the second web M8, and the fibers are bonded to each other via the molten composite C10. This forms a sheet S as a molded body. Then, this sheet S is transported toward the cutting section 21. Note that one of the pair of heating rollers 204 is a driven roller driven by the operation of a motor (not shown), and the other is a driven roller.
[0152] The cutting unit 21 is disposed downstream of the sheet forming unit 20. The cutting unit 21 is a portion that performs a cutting step of cutting the sheet S. The cutting unit 21 has a first cutter 211 and a second cutter 212.
[0153] The first cutter 211 cuts the sheet S in a direction intersecting the conveying direction of the sheet S.
[0154] The second cutter 212 is located downstream of the first cutter 211 and cuts the sheet S in a direction parallel to the conveying direction of the sheet S.
[0155] The sheet S is obtained as a compact having a desired size by cutting with the first cutter 211 and the second cutter 212. The sheet S is then transported further downstream and accumulated in the stock section 22.
[0156] [3] Molded body Next, the molded article according to the present invention will be described.
[0157] The molded article according to the present invention is produced by the above-mentioned method for producing a molded article according to the present invention. This makes it possible to provide a molded article that contains fibers and has excellent strength.
[0158] The fibers, binding material, and inorganic particles contained in the molded article according to the present invention preferably satisfy the same conditions as those explained in [1-1-1], [1-1-2-1-1], and [1-1-2-1-2] above, respectively.
[0159] The shape of the molded product according to the present invention is not particularly limited and may be any shape, such as a sheet, a block, a sphere, or a three-dimensional shape, but the molded product according to the present invention is preferably in the form of a sheet. Note that the sheet shape referred to here means a shape having a thickness of 30 μm to 30 mm and a density of 0.05 g / cm. 3 More than 1.5g / cm 3 This refers to a molded body molded as follows:
[0160] This allows the molded article to be suitably used as, for example, a recording medium, etc. Furthermore, by using the above-mentioned device, the molded article can be produced more efficiently.
[0161] When the molded article according to the present invention is a sheet-shaped recording medium, its thickness is preferably 30 μm or more and 3 mm or less.
[0162] This allows the molded article to be more suitably used as a recording medium. Also, by using the above-mentioned apparatus, the molded article can be produced more efficiently.
[0163] When the molded article according to the present invention is a sheet-shaped recording medium, its density is 0.6 g / cm 3 More than 0.9g / cm 3 It is preferable that: This allows the molded article to be more suitably used as a recording medium.
[0164] The molded article according to the present invention may be at least partially manufactured by applying the above-mentioned manufacturing method of the molded article according to the present invention, and may further include other parts. Also, the molded article according to the present invention may be subjected to post-treatment after the steps described in the manufacturing method of the molded article according to the present invention.
[0165] The uses of the molded article according to the present invention are not particularly limited, and examples thereof include recording media, liquid absorbents, cushioning materials, and sound absorbing materials.
[0166] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to these.
[0167] For example, in the above-described embodiment, the composite was mainly described as including composite particles having inorganic particles attached to the surfaces of binding material particles, but the composite may not include the composite particles described above as long as it includes binding material particles and inorganic particles.
[0168] In the above embodiment, the inorganic particles constituting the composite body are mainly described as inorganic base particles that have been surface-treated with a surface treatment agent, but the inorganic particles may not be surface-treated with a surface treatment agent. In this case, it is preferable that the inorganic particles satisfy the same conditions as those described in [1-1-2-1-2-1] above.
[0169] In addition, each part constituting the sheet manufacturing apparatus may be replaced with any other part capable of exerting the same function. In addition, any other component may be added.
[0170] Furthermore, the molded article according to the present invention is not limited to one produced using the above-mentioned apparatus, and may be one produced using any apparatus. EXAMPLES
[0171] Next, specific examples of the present invention will be described. [4] Preparation of the complex (Preparation Example 1) First, starch (NSP-EA, manufactured by Nippon Starch Chemical Co., Ltd.) having a weight average molecular weight of 100,000 as a binding material was pulverized to an average particle size of 3.0 μm using a pulverizer (Counter Jet Mill AFG-CR, manufactured by Hosokawa Micron Corporation).
[0172] Thereafter, the ground starch was loaded into a Henschel mixer (FM mixer (FM 20C / I) manufactured by Nippon Coke Company), and 1 part by mass of fumed silica (DM-10 manufactured by Tokuyama Corporation) having dimethylsilyl groups on the surface as inorganic particles was added per 100 parts by mass of starch, followed by stirring at 6,000 rpm for 1 hour to prepare a composite.
[0173] The composite thus obtained contained composite particles in which the inorganic particles, fumed silica, were attached to the surfaces of the binding material particles, starch particles. The average particle size of the inorganic particles contained in the composite was 14 nm, and the average particle size of the binding material particles contained in the composite was 3.0 μm.
[0174] (Preparation Examples 2 to 15) A composite was prepared in the same manner as in Preparation Example 1, except that the types of binding material and inorganic particles used as raw materials were as shown in Table 1, and the crushing conditions of the binding material and the compounding ratio of the binding material particles and the inorganic particles were adjusted to obtain the composition shown in Table 1.
[0175] A composite was prepared in the same manner as in Preparation Example 1, except that the types of binding material and inorganic particles used as raw materials were as shown in Table 1, and the crushing conditions of the binding material were adjusted to obtain the composition shown in Table 1.
[0176] The composition of the composites obtained in each of the above Preparation Examples is summarized in Table 1. In Table 1, starch with a weight-average molecular weight of 100,000 (NSP-EA, manufactured by Nippon Starch Chemical Co., Ltd.) is designated as "NSP-EA," dextrin with a weight-average molecular weight of 20,000 (MF-30, manufactured by Nippon Starch Chemical Co., Ltd.) is designated as "MF-30," soft starch with a weight-average molecular weight of 600,000 (SF-930, manufactured by Sanwa Starch Co., Ltd.) is designated as "SF-930," and fumed silica (DM-10, manufactured by Tokuyama Corporation), which is an inorganic particle having a mean particle size of 14 nm and having dimethylsilyl groups on the surface, is designated as "SF-930." "DM-10", fumed silica (Tokuyama Corporation, HM-30S), inorganic particles having a mean particle size of 7 nm and having trimethylsilyl groups on the surface, is shown as "HM-30S", fumed silica (Tokuyama Corporation, ZD-30ST), inorganic particles having a mean particle size of 7 nm and having trimethylsilyl groups on the surface, is shown as "ZD-30ST", fumed alumina (Nippon Aerosil Co., Ltd., AEROXIDE Alu-C), inorganic particles having a mean particle size of 7 nm and having trimethylsilyl groups on the surface, is shown as "AluC", and fumed titania (Nippon Aerosil Co., Ltd., AEROXIDE NKT 90), inorganic particles having a mean particle size of 7 nm and having trimethylsilyl groups on the surface, is shown as "NKT90". In addition, in Table 1, a composition consisting of only binding material particles having a mean particle size of 10 μm prepared in the same manner as described in Preparation Example 1 is shown as Preparation Example 16. In addition, in all of Preparation Examples 1 to 15, the proportion of the binding material particles constituting the composite particles to the total binding material particles contained in the composite was 90 mass% or more, and the proportion of the inorganic particles constituting the composite particles to the total inorganic particles contained in the composite was 90 mass% or more.
[0177] [Table 1]
[0178] [5] Manufacturing of sheets as molded bodies Example 1 In this example, the composite prepared in Preparation Example 1 was used to produce a sheet as a molded article in the following manner.
[0179] First, a sheet manufacturing apparatus as shown in FIG. 2 was prepared, and commercially available copy paper (GR70-W, manufactured by Fuji Xerox Co., Ltd.) was prepared as a sheet material serving as a fiber source.
[0180] Next, the above sheet-like material was supplied to the raw material supply section of the sheet manufacturing apparatus, and the composite prepared in Preparation Example 1 was supplied to the composite supply section. The sheet manufacturing apparatus was operated, and the processes of the coarse crushing process, defibrating process, sorting process, first web forming process, dividing process, mixing process, loosening process, second web forming process which is a stacking process, humidifying process, sheet forming process which is a molding process, and cutting process were carried out to produce an A4 size sheet as a molded product. The basis weight of the obtained sheet was 90 g / m 2 It was.
[0181] At this time, the sheet as the final molded product was adjusted to contain 90 parts by mass of fiber and 10 parts by mass of the composite as raw materials. In the moistening step, 20 parts by mass of moisture was added to 100 parts by mass of the mixture to be subjected to the moistening step. The heating temperature when heating and pressing in the heating section was 80°C, the pressure when heating and pressing in the heating section was 70 MPa, and the heating and pressing time when heating and pressing in the heating section was 15 seconds.
[0182] (Examples 2 to 16) An A4-sized sheet was produced as a molded body in the same manner as in Example 1, except that the composite shown in Table 2 was used and the amount of moisture added to 100 parts by mass of the second web formed by stacking the mixture of fibers and composites, i.e., the amount of moisture added to 100 parts by mass of the mixture subjected to the moistening process, was adjusted as shown in Table 2.
[0183] Comparative Example 1 An A4 size sheet was produced as a molded article in the same manner as in Example 2, except that the second web formed by depositing the mixture of fibers and composite was not moistened.
[0184] Comparative Example 2 An A4 size sheet was produced as a molded body in the same manner as in Example 1, except that the composite was replaced with the composition of Preparation Example 16, i.e., a composition consisting only of binder particles having an average particle size of 10 μm prepared in the same manner as described in Preparation Example 1. The manufacturing conditions for the molded bodies of the above-mentioned Examples and Comparative Examples are shown in Table 2.
[0185] [Table 2]
[0186] [6] Evaluation [6-1] Strength of molded body From the sheets as the molded bodies produced in each of the Examples and Comparative Examples, strips of 100 mm x 20 mm were cut out, and the breaking strength was measured in the longitudinal direction of the strips. The breaking strength was measured using an autograph AGS-1N manufactured by Shimadzu Corporation at a pulling speed of 20 mm / sec, from which the specific tensile strength was calculated and evaluated according to the following criteria. It can be said that the higher the specific tensile strength, the better the strength.
[0187] A: The specific tensile strength is 25 Nm / g or more. B: The specific tensile strength is 20 Nm / g or more and less than 25 Nm / g. C: The specific tensile strength is 15 Nm / g or more and less than 20 Nm / g. D: The specific tensile strength is 10 Nm / g or more and less than 15 Nm / g. E: The specific tensile strength is less than 10 Nm / g.
[0188] [6-2]Liquidity The repose angle and compressibility of the composites used to manufacture the molded bodies in each of the above Examples and Comparative Example 1, and the composition consisting of the binder particles used to manufacture the molded body in Comparative Example 2 were measured using a powder property evaluation device (Powder Tester PT-X, manufactured by Hosokawa Micron Corporation).
[0189] From these measurement results, the fluidity value, which is the product of the angle of repose [°] and the degree of compressibility [%], was calculated and evaluated according to the following criteria. The smaller the fluidity value, the better the fluidity.
[0190] A: The liquidity value is less than 10. B: The fluidity value is 10 or more and less than 12. C: Fluidity value is 13 or more and less than 14. D: Fluidity value is 14 or more but less than 17. E: Fluidity value is 17 or more. These results are summarized in Table 3.
[0191] [Table 3]
[0192] As is clear from Table 3, excellent results were obtained in the present invention. In contrast, satisfactory results were not obtained in the comparative examples.
[0193] In addition, composites were produced in the same manner as in the above-mentioned Examples, except that the mixing ratio of the fibers and the composite in the deposition step was changed in various ways so that the content of the composite in the mixture obtained in the deposition step was 1% by mass or more and 50% by mass or less, and the same evaluation was performed on these composites as described above, and the same results were obtained. In addition, composites were produced in the same manner as in the above-mentioned Examples, except that the heating temperature in the molding step was changed in various ways within the range of 60°C or more and 250°C or less, and the same evaluation was performed on these composites as described above, and the same results were obtained. In addition, composites were produced in the same manner as in the above-mentioned Examples, except that the pressure applied to the mixture in the molding step was changed in various ways within the range of 0.1 MPa or more and 100 MPa or less, and the same evaluation was performed on these composites as described above, and the same results were obtained. In addition, composites were produced in the same manner as in the above-mentioned Examples, except that the heating and pressurizing time in the molding step was changed in various ways within the range of 1 second or more and 60 seconds or less, and the same evaluation was performed on these composites as described above, and the same results were obtained. [Explanation of symbols]
[0194] 100...sheet manufacturing apparatus, 11...raw material supply section, 12...crushing section, 121...crushing blade, 122...hopper, 13...defibrating section, 14...screening section, 141...drum section, 142...housing section, 15...first web forming section, 151...mesh belt, 152...tension roller, 153...suction section, 16...fragmenting section, 161...propeller, 162...housing section, 17...mixing section, 171...composite supply section, 172...pipe, 173...blower, 174...screw feeder, 18...loosening section, 181...drum section, 182...housing section, 19...second web forming section, 191...mesh belt, 192...tension roller, 193...suction section, 20...sheet forming section, 201...pressure section, 202...heating section, 20 3...calender roller, 204...heating roller, 21...cutting section, 211...first cutter, 212...second cutter, 22...stock section, 231...humidifying section, 232...humidifying section, 233...humidifying section, 234...humidifying section, 235...humidifying section, 236...humidifying section, 241...tube, 242...tube, 243...tube, 244...tube, 245...tube, 246...tube, 261 ...blower, 262...blower, 263...blower, 27...recovery section, C10...composite, C1...composite particles, C2...binding material particles, C3...inorganic particles, M1...sheet-like material, M2...coarsely crushed pieces, M3...defibrated material, M4-1...first sorted material, M4-2...second sorted material, M5...first web, M6...fragmented body, M7...mixture, M8...second web, S...sheet
Claims
1. depositing a mixture comprising fibers and composites; a humidifying step of humidifying the mixture; and a molding step of heating and pressurizing the humidified mixture to obtain a molded body, The composite includes composite particles that integrally include binding material particles containing a binding material that exhibits a bonding force to bond the fibers together when moisture is added, and inorganic particles having trimethylsilyl groups on their surfaces.
2. The method for producing a molded article according to claim 1 , wherein the binder material is starch having a weight average molecular weight of 50,000 or more and 400,000 or less.
3. The method for producing a molded body according to claim 1 or 2, wherein the average particle size of the binder material particles is 1.0 μm or more and 50 μm or less.
4. The method for producing a molded article according to claim 1 , wherein the inorganic particles are made of a material containing silica.
5. The method for producing a molded article according to claim 1 , wherein the inorganic particles have an average particle size of 1 nm or more and 20 nm or less.
6. The method for producing a molded article according to claim 1 , wherein the composite contains composite particles in which the inorganic particles are attached to surfaces of the binder particles.
7. The method for producing a molded article according to claim 1 , wherein a content of the inorganic particles in the composite is from 0.1% by mass to 10.0% by mass.
8. The method for producing a molded article according to claim 1 , wherein the inorganic particles have polydimethylsiloxane having trimethylsilyl terminals on the surface thereof.
9. The method for producing a molded body according to claim 1 , wherein in the humidifying step, 1 part by mass or more and 50 parts by mass or less of water is added to 100 parts by mass of the mixture subjected to the humidifying step.
10. The method for producing a molded article according to claim 1 , wherein a content of the composite in the mixture is from 1% by mass to 50% by mass.
Citation Information
Patent Citations
Manufacture of recycled article such as cushioning material, etc. using old papers
JP1993246465A
Paper, method for manufacturing same, support for image recording material, and image recording material
JP2005070753A
Sheet production apparatus
JP2015203163A
Sheet production device and sheet production method
JP2016145427A
Molding material for manufacturing fibrous molded article and molded article using the same
JP2018016745A